HUBUNGAN ANTARA PERCERAIAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Nanda Arumi Handayani; Siti Masyithoh (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2023)
This study has the objective of explaining the relationship between parental divorce and the learning motivation of elementary school students. The method used in this study is a descriptive qualitative method with a literature study approach. Data collection techniques are carried out by gathering sources related to the topic raised. Data analysis was carried out by reducing data, analysing and synthesizing linkages and interpretations according to the research objectives. So that the results obtained are that the divorce of parents has a negative influence on elementary school students, namely: 1) giving less affection from both parents, 2) achievement and low enthusiasm for learning, 3) low self-confidence and social skills, and 4) Self-regulation is also low. Divorce has a bad influence on the social environment, life and motivation and student achievement. Children's emotions are so influential on children's learning activities, such as feelings of joy, security, fear, anxiety, anger and sadness.